Competition for soil water among trees, shrubs and pasture in Iberian Dehesas. Consequences for pasture and tree productivity - Moreno G.; Rolo V.; Cubera E. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The low tree density in silvopastoral systems results in increased pasture productivity and allows remnant trees to cope with summer water deficit. However, the worldwide phenomenon of savanna shrub encroachment could compromise the benefit of wide tree spacing in these water limited forests. We analyze the effect of shrub encroachment of Iberian dehesas for soil water dynamic and tree water status. The consequences for oak tree and pasture productivity are discussed. Increased tree density resulted in a worsening of tree water status and acorn productivity. Cistus shrubs showed a net competitive effect for soil water which influenced negatively the pasture yield, and the functional state and acorn production of the trees. By contrast, Retama shrubs affected positively the soil moisture of uppermost soil layers (hydraulically lifted water) and showed a facilitative effect for pasture yield without influencing the functional tree state and acorn production.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)